Translation and cultural adaptation of the Pediatric Eosinophilic Esophagitis Symptom Score (PEESS v2.0) - Maria Fernanda Oliveira Santos; Cristina Palmer Barros; Carlos Henrique Martins da Silva; Helena Borges Martins da Silva Paro (Brazilian Society of Pediatrics, 2018)
Objectives: To translate and culturally adapt the Pediatric Eosinophilic Esophagitis Symptom Score (version 2.0), a tool used to assess pediatric eosinophilic esophagitis symptoms reported by patients and/or their parents/caregivers. Methods: The Pediatric Eosinophilic Esophagitis Symptom Score was translated through the following stages: initial translation, back‐translation, and consensus of independent reviewers through the Delphi technique. The pre‐final version of the Pediatric Eosinophilic Esophagitis Symptom Score was applied to five 8‐to‐18‐year‐old patients and to ten parents of two‐to‐18‐year‐old patients from an outpatient pediatric gastroenterology service (pre‐test). Results: During the translation process, no translations presenting with difficult consensus in the review process or grammar inconsistencies were observed. During the pre‐test, difficulties in comprehension of some unconventional terms, e.g., "náusea", were observed. Adverbs of frequency, such as "quase nunca" were also identified as being of difficult understanding by patients and parents, and the substitution by the term "raramente" was suggested. Such difficulties may be inherent to the pediatric age group. Age 8 years or above should be considered adequate for the self‐reporting of symptoms. Conclusions: The study presents the Brazilian version of the Pediatric Eosinophilic Esophagitis Symptom Score, which is adapted to the Brazilian culture. This version may be introduced as a clinical and research tool for the assessment of patients with esophagic disease symptoms. The Pediatric Eosinophilic Esophagitis Symptom Score is a breakthrough in the evaluation of symptoms of pediatric eosinophilic esophagitis, since it reinforces the importance of self‐reporting by patients who experience this disease. Resumo: Objetivo: Traduzir e adaptar culturalmente a Pediatric Eosinophilic Esophagitis Symptom Score (versão 2.0), um instrumento usado para identificar os sintomas relatados pelos pacientes ou seus pais/responsáveis para a avaliação da esofagite eosinofílica pediátrica. Método: Realizamos o processo de tradução a partir da tradução inicial, retrotradução, seguida da etapa de obtenção de consenso por revisores independentes por meio da técnica Delphi. Aplicamos a versão pré‐final a cinco pacientes de 8 a 18 anos e dez pais de pacientes de 2 a 18 anos no Serviço de Gastroenterologia Pediátrica (pré‐teste). Resultados: No processo de tradução, não encontramos traduções de difícil consenso no processo de revisão ou discordâncias gramaticais. No pré‐teste, identificamos dificuldades de entendimento de termos pouco convencionais, como "náusea", com sugestão de substituição para o termo "enjoo". Outra dificuldade encontrada relacionou‐se aos advérbios de frequência da escala, como, por exemplo, "quase nunca", foi sugerida a substituição pelo termo "raramente". Essas dificuldades podem ser inerentes à faixa etária pediátrica. A idade dos pacientes a partir de oito anos deve ser considerada adequada para o uso de escores de autorrelato. Conclusões: A tradução do escore de sintomas da esofagite eosinofílica pediátrica produziu uma escala adaptada à cultura brasileira, que poderá ser introduzida como instrumento de investigação clínica e de pesquisa em pacientes com sintomas sugestivos de doenças esofágicas. É um importante avanço na avaliação dos sintomas, já que valoriza o relato dos próprios pacientes que convivem com essa doença. Keywords: Eosinophilic esophagitis, Translations, Self‐report, Child, Adolescent, Palavras‐chave: Esofagite eosinofílica, Traduções, Autorrelato, Criança, Adolescente